An extended validation of the Communal Coping Strategies Inventory for Competitive Team Sports: A multilevel approach. (March 2023) - Pété, Emilie; Chanal, Julien; Doron, Julie
Abstract: A questionnaire that can properly measure communal coping in sport is required to further investigate and understand how individuals in a team collectively cope with stressful sport situations. The Communal Coping Strategies Inventory for Competitive Team Sports (CCSICTS; Leprince et al., 2019) needed to be validated at the collective level and in its situational form to be used in broader sport situations. The aims of the present work were to improve and further validate the factorial structure of the CCSICTS at both individual and team levels. With a sample of 380 French athletes, representing 56 teams, Study 1 showed support for a multilevel, hierarchical and four-dimensional factorial structure of the revised version of the CCSICTS at both individual and team levels. With a sample of 641 French athletes, representing 75 teams, Study 2 confirmed the factorial structure obtained in Study 1 at individual and team levels, and its validity in sport-specific situations. The results of both studies also highlighted a bifactorial structure, allowing interpretation of communal coping as an overall team capacity to adapt to stress. As such, the psychometric qualities of the CCSICTS-R have been established at individual and team levels. The CCSICTS-R enables proper and distinct measurement of the characteristics of communal coping in sport (i.e., hierarchical, multidimensional, multilevel, both situational and dispositional) and can be used from both research and practical perspectives. Highlights: The aim was to further validate a questionnaire measuring communal coping in sport (i.e., CCSICTS). The multilevel factorial validity of the CCSICTS-R was established. The CCSICTS-R can be used in both dispositional and situational forms. Communal coping may be viewed as the overall team capacity to adapt to stress. This tool can be used to evaluate how teams cope with stress, from research and practical perspectives.